Small producer organizations, certifications, and competitiveness: recent experience in Costa Rica - Díaz Porras, Rafael Antonio (2016)
This article investigates whether the application of environmental certifications has led to improved competitiveness among small and medium-sized agricultural producers. To this end, it analyzes the certification environment both internationally and within Costa Rica's institutional framework, and examines the realities of small producer organizations' experiences based on the results of a survey conducted in 2015The article concludes that the certification strategy has enabled better positioning and, consequently, stability in the value chain, although for organizations and policy-making bodies there are areas for improvement, such as costs and changes in processes and cultural resistance to this type of initiative.